Strategy for Increasing Original Regional Income (PAD) Through the Hotel and Restaurant Tax Sector in Kupang City Post the Covid-19 Pandemic - Sabuna, Adelheid; Hanafi, Imam (Journal of Public Administration and Government, 2024)
Unique Territorial Pay (Cushion) is local pay obtained from provincial charges, territorial tolls, isolated territorial abundance the executives results, and other genuine local pay. Inn and Eatery Expense is remembered for the 11 territorial charges gathered by the regional government. The research aims to first ascertain the growth ratio, effectiveness, and contribution level of hotel and restaurant tax revenues in Kupang City prior to, during, and following the Covid-19 pandemic, and then to devise a strategy for planning an expansion of Kupang City's PAD. The examination will be completed utilizing 4 monetary proportions and SWOT examination to decide the system for expanding nearby income from the lodging and café charge area in Kupang City. The kind of information utilized is auxiliary and essential information as Kupang City provincial pay for the 2017-2022 period. The exploration results observed that the normal territorial monetary freedom proportion was just 22.48%, this shows that the City of Kupang is still extremely reliant upon reserves obtained from the focal and commonplace state run administrations. The commitment of neighborhood charges to Kupang City's Cushion will in general vary. The Kupang City government's financial performance in managing hotel tax revenues is demonstrated by the effectiveness ratio of restaurant and hotel tax revenues. The Cushion development proportion and all out lodging and eatery charge income likewise show fluctuating development. The commitment of inn and eatery charge incomes to Unique Territorial Pay over a time of six years didn't have a critical commitment. The procedure to build Cushion through the inn and café charge area during the pandemic is the StrengthOpportunity (SO) methodology, specifically by utilizing interior qualities to make the most of existing outside amazing open doors. There are 4 procedures planned.